Partial Maxillectomy for the Improvement of Nasal Obstruction Can Be Combined with Septorhinoplasty - Weber, Rainer K.; Giotakis, Evangelos I.; Hildenbrand, Tanja; Heppt, Werner (Facial Plastic Surgery, 2021)
We describe the (anteromedial) partial maxillectomy technique which can be used to address impaired nasal breathing in cases of significant protrusion of the frontal process of the maxilla into the nasal cavity, narrowing the nasal pathway. It fits to nasal physiology avoiding mucosal resection. It can be combined with surgery of the inferior turbinate. The described technique can be used in all forms of rhinoplasty.
Keywords: partial maxillectomy; nasal obstruction; inferior nasal turbinate; lateral nasal wall; frontal process of the maxilla; septorhinoplasty